2020
DOI: 10.21203/rs.2.11384/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tuberculosis among economic migrants: A cross‐sectional study of the risk of poor treatment outcomes and impact of a treatment adherence intervention among temporary residents in an urban district in Ho Chi Minh City, Viet Nam

Abstract: Background: Tuberculosis (TB) remains a major cause of avoidable deaths. Economic migrants represent a vulnerable population due to their exposure to medical and social risk factors. These factors expose them to higher risks for TB incidence and poor treatment outcomes. Methods: This cross-sectional study evaluated WHO-defined TB treatment outcomes among economic migrants in an urban district of Ho Chi Minh City, Viet Nam. We measured the association of a patient’s government-defined residency status with trea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As defined in the End TB strategy, the 2020 TB treatment success rate target is at least 90% [2]. Generally, TB treatment success in the refugee population can be affected by factors including less adherence to treatment, death, noncompletion due to lost to follow-up (LTFU), malnutrition, and other coexisting illnesses such as HIV coinfection [8,20,21]. Studies showed lower treatment success rate among refugees in Ethiopia (75.1%) [22] and in refugees hosted in different countries (ranging from 63.6 to 77.5%) [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As defined in the End TB strategy, the 2020 TB treatment success rate target is at least 90% [2]. Generally, TB treatment success in the refugee population can be affected by factors including less adherence to treatment, death, noncompletion due to lost to follow-up (LTFU), malnutrition, and other coexisting illnesses such as HIV coinfection [8,20,21]. Studies showed lower treatment success rate among refugees in Ethiopia (75.1%) [22] and in refugees hosted in different countries (ranging from 63.6 to 77.5%) [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with their older age, immigrants with TB had lower levels of education, higher prevalence of diabetes and lower BCG vaccination. TB immigrants worldwide are less likely to have treatment success, due in part to their higher likelihood of treatment interruption 24 . After adjustment, abandonment of treatment was higher.…”
Section: Discussionmentioning
confidence: 99%